1996
DOI: 10.1021/jf950258m
|View full text |Cite
|
Sign up to set email alerts
|

Production of a Sensitive Monoclonal Antibody to Sterigmatocystin and Its Application to ELISA of Wheat

Abstract: A hybridoma cell line capable of secreting sensitive and specific monoclonal antibody for sterigmatocystin (STG) was produced by fusing SP2/0 myeloma cells with spleen cells of female Balb/C mice immunized with STG hemiacetal-bovine serum albumin conjugate. The concentration of STG required to inhibit 50% of the binding of the monoclonal antibody in a competitive ELISA (cELISA) was 2.5 ng/mL. The apparent affinity dissociation constant of the monoclonal antibody was 2.3 × 10 -9( 1.4 × 10 -10 M -1 . The cross-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Only a very limited number of enzyme-linked immunoassay (ELISA) methods have been described for STC, making use of either polyclonal (Morgan et al, 1986;Olson and Chu, 1993a) or monoclonal antibodies (Li et al, 1996). In wheat, the lowest reproducible concentration of STC that could be quantified was 31 µg/kg, with a working range up to 250 µg/kg (Li et al, 1996).…”
Section: Immunochemical Methodsmentioning
confidence: 99%
“…Only a very limited number of enzyme-linked immunoassay (ELISA) methods have been described for STC, making use of either polyclonal (Morgan et al, 1986;Olson and Chu, 1993a) or monoclonal antibodies (Li et al, 1996). In wheat, the lowest reproducible concentration of STC that could be quantified was 31 µg/kg, with a working range up to 250 µg/kg (Li et al, 1996).…”
Section: Immunochemical Methodsmentioning
confidence: 99%
“…) or lacked sensitivity (Li et al . ), and were obviously not further studied. More recently, Li et al .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, rapid immunochemical screening tests, as available for the aflatoxins, do not exist. Approaches to establish enzyme immunoassays (EIA) based on antibodies against STC-hemiacetal as the antigen were reported some decades ago, but these either required tedious chemical conversion of STC into its hemiacetal before detection (Li and Chu 1984;Morgan et al 1986;Lou et al 1996) or lacked sensitivity (Li et al 1996), and were obviously not further studied. More recently, Li et al (2014) reported monoclonal antibodies against STC, employing a method originally described for AFB 2 by Cervinio et al (2007), and their use in competitive indirect EIA.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (1996) developed a sensitive monoclonal antibody for STC and applied it in an enzyme-linked immunosorbent assay (ELISA) for STC quantification in wheat. Among chromatographic methods, thin layer chromatography has been widely used as a technique for STC analysis (AOAC 2005;Versilovskis and De Saeger 2010).…”
Section: Introductionmentioning
confidence: 99%